Women’s knowledge, attitude, and practice regarding cervical precancerous lesions: a cross-sectional study in Beijing, China - Wang, Lingyan; Wang, Qianping; Zhou, Xia; Liu, Huan (Frontiers in Public Health, 2024)
Background This study aimed to examine the knowledge, attitude, and practice (KAP) of women in Beijing regarding cervical precancerous lesions. Methods This web-based, cross-sectional study included women at Dongzhimen Hospital of Beijing University of Chinese Medicine between March 13, 2024 and April 9, 2024. A self-administered questionnaire was developed to collect participants’ demographic information and KAP scores toward cervical precancerous lesions. Results The study included 951 valid questionnaires, with a mean age of 40.0 years. The mean knowledge, attitude, and practice scores were 12.55 ± 6.23 (possible range: 0–26), 50.66 ± 7.48 (possible range: 13–65), and 26.13 ± 4.98 (possible range: 7–35), respectively. The knowledge score (OR = 1.071, 95%CI: 1.040–1.103, p < 0.001), currently married (OR = 0.548, 95%CI: 0.304–0.985, p = 0.045), and with a history of HPV infection (OR = 2.302, 95%CI: 1.062–4.990, p = 0.035) were independently associated with the attitude score. The knowledge score (OR = 1.155, 95%CI: 1.119–1.192, p < 0.001), monthly income >20,000 (OR = 2.793, 95%CI: 1.249–6.248, p = 0.012), a history of HPV infection (OR = 0.380, 95%CI: 0.222–0.650, p < 0.001), unknown HPV infection status (OR = 0.289, OR = 0.177–0.473, p < 0.001), vaccinated against HPV (OR = 1.752, 95%CI: 1.221–2.514, p = 0.002), giving birth to one child (OR = 1.991, 95%CI: 1.186–3.341, p = 0.009), and giving birth to two or more children (OR = 2.160, 95%CI: 1.240–3.763, p = 0.007) were independently associated with the practice score. The structured equation model showed that knowledge directly influenced attitude (β = 0.237, p = 0.004) and practice (β = 0.490, p = 0.010). Attitude directly influenced practice (β = 0.193, p = 0.009). Conclusion This study revealed inadequate knowledge, moderate attitude, and practice toward cervical precancerous lesions among women in Beijing. Educational interventions should be developed to enhance knowledge in this regard.